Study of prevalence of hypertension and its various risk factor in type 2 diabetes mellitus patients - Uma, Narendra M.; Parmar, Mahendra C.; Shah, Siddarth; Dindod, Sonal M. (International Journal of Advances in Medicine, 2019)
Background: Surgical diabetes is syndrome of hyperglycemia and disturbance of carbohydrate, fat and protein metabolism associated with absolute or relative deficiency of insulin secretions. Diabetes mellitus and hypertension considered as a major medical and public health issues worldwide, and both are important risk factors for both macrovascular and microvascular diseases like coronary artery disease, heart failure and cerebrovascular diseases. Methods: This cross-sectional study was conducted among 175 patients coming to Govt. medical college and SSG hospital, Vadodara from 2014 to 2015 having diabetes mellitus were studied and evaluated for hypertension and its various risk factor like age, obesity. Results: one hundred and twenty-nine (127) out of 175 subjects had hypertension, thus giving a prevalence rate of 73.7% of which 64 males (49.6%) were hypertensive compared with 65 (50.3%) females. Mean age of patients having hypertension with Diabetes Mellitus (case) is 59.87 compare to DM without hypertension (control) was 56.21. Mean BMI in diabetes cases with hypertension was 30.93 while without hypertension was 23.47 suggest obese are more prone to develop hypertension. Waist hip ratio DM with hypertension was 0.96 while was 0.81 in DM without hypertension. Conclusion: Hypertension and its associated risk factor like obesity, dyslipidemia are important risk factor for development of complication in diabetes patients so early detection and intervention measures should be undertaken for aggressive control of blood pressure control , obesity and it will likely to offer the greatest promise for reducing the incidence of complications and its associated mortality.